Schistosomiasis Involving the Central Nervous System: Case Report of a Rare Complication - Rahaf F. Alanazi; Maryam Al Karawi; Abdulrahman Almalki; Fahd Sufiani; Sarmad Al Karawi (Case Reports in Surgery)
Introduction. Schistosomiasis is a parasitic infection caused by schistosome invasion of blood circulation. Neuroschistosomiasis is a severe cerebral complication that accounts for less than 2.3% of reported cases. Patients present with progressive encephalitis, seizures, or both. Management includes antiparasitic medications, steroids, and surgical intervention. Case Presentation. We report a case of a 44-year-old female who presented to the ER with a history of transient loss of consciousness (LOC) and seizure. Radiological investigations revealed a right frontal brain lesion. Histopathological results confirmed the diagnosis of schistosomiasis. Conclusion. Schistosomiasis is a parasitic infection commonly diagnosed in patients who live in tropical areas. Early diagnosis with radiological and histopathological evaluation is required to identify patients at risk of developing severe neurological complications.